Stress Management Strategies: An In-Depth Study of IT Professionals in Chennai - Ayare, Kundan Mahadev; Agarwal, Sarthak; S, Deepajothi (International Journal of Computer Sciences and Engineering, 2025)
In the swiftly advancing information technology (IT) business, stress management is essential for maintaining productivity, mental health, and overall job happiness. This study examines the stress levels of IT professionals in Chennai, a prominent technological hub, to comprehend the issues encountered in this high-pressure business. The study utilizes primary data obtained from structured surveys and secondary research from existing literature to identify significant stressors, including excessive workloads, prolonged working hours, and inadequate work-life balance. The study investigates the efficacy of diverse stress management strategies, such as mindfulness practices, consistent physical activity, meditation, and yoga, in mitigating stress. The analysis examines the impact of organizational assistance, including flexible work schedules and counseling services, on mitigating workplace stress. The results underscore the imperative of adopting customized stress management measures in corporate settings to cultivate a healthier and more efficient workforce.